Witnesses of the Time: A survey of clock rooms, clock towers and façade clocks in Istanbul in the Ottoman Era - Kaan Üçsu (Rúbrica Contemporánea, 2017)
The Ottoman Empire used an hour system based on the motion of the sun and, accordingly, on seasonal hours, inherited from earlier Islamic countries. Later on, the introduction and the spread of mechanical clocks made develop a unique and hybrid hour system, called alla turca, based both on the motion of the sun and on equal hours. From the late 18th century onwards, the imperial capital Istanbul witnessed constant reformation projects where the time discipline was an essential part. Finally, the acquaintance with the meantime and their use together with alla turca in the latter part of the 19th century called for new regulations and arrangements. In order to announce these different systems, the state needed various means. In this context, this contribution aims to survey the means used to inform the actors: the clock rooms, the clock towers and the façade clocks in Istanbul during the Ottoman era. While doing this, it tries to understand the context where they were constructed, erected or installed.